ВИЗНАЧЕННЯ ДЕКОРАТИВНОСТІ ТА УСПІШНОСТІ ІНТРОДУКЦІЇ ВИДІВ РОДУ FORSYTHIA VAHL. В УМОВАХ БІОСТАЦІОНАРУ ВНАУ - Матусяк, М. В.; Варгатюк, О. В. (Вісник Уманського національного університету, 2023)
The article is devoted to the development of project proposals for the creation of a square in Khortytsky district of Zaporizhzhya. To determine the possibility of placing a square in the territory between multi-storey buildings, we conducted all the necessary pre-project research. Soil conditions have been surveyed by indicators such as mechanical composition, acidity of the soil solution, colour and structure of soil. An inventory of existing plantations was carried out on the basis of geodetic materials, engineering networks, buildings and structures. The evaluation of the compositional and aesthetic aspects of the landscape was performed in the field on the basis of personal impressions. The square will have mixed- style features, that combines the features of a regular and free (landscape) planning. The whole territory of the square is conditionally divided into two functional areas – a dog training ground and an area for walking and relaxation. The Central part of the park will be decorated with a dry fountain, which will freshen the air on a hot day, tracing the paths will take the form of a triangle, which will allow to combine three entrances of the territory of the arboretum between themselves and with central part. In the northwestern part it is planned to place a training ground for dogs, the rest part of the territory will be offered for their recreation on grassy lawns among the flowering shrubs. The project is planned landing of the 7 species of trees and 10 species of shrubs, total number 62 and 389 copies. respectively. These are the types of plants, like Aesculus hippocastanum, Tilia cordata, Picea pungens, Pinus silvestris, Pinus mugo, Thuja occidentalis, Syringa vulgaris, Syringa josikaea, Syringa chinensis, Syringa persica, Forsythia europaea, Spiraea japonica, Juniperus sabina, Juniperus horizontalis.The enrichment of the species diversity of plants and increasing in fullness of the plantings will significantly reduce the harmful factors of urbanization. The creation of recreation area under the proposed project will partially compensate for the lack of green spaces in residential areas and improve the general sanitary-hygienic and ecological status of the area.Згідно отриманих результатів досліджень встановлено, що на території Вінницького НАУ рід Forsythia Vahl. представлений 5 видами, найбільш поширені з них: Forsythia suspensa (Thunb.) Vahl (близько 47 %), Forsythia europaea Degen & Bald (23 %), дещо менше поширені такі види як: Forsythia ovata Nakai (12 %), Forsythia × intermedia (10 %), Forsythia viridissima Lindl. (8 %).Досліджено, що в умовах м. Вінниці найбільш високим акліматизаційним числом характеризуються види Forsythia suspensa (Thunb.) Vahl., Forsythia ovata Nakai (85 і 87 балів відповідно), найнижчим акліматизаційним числом характеризуються Forsythia giraldiana, Forsythia suspense «Variegata» (Thunb.) Vahl, Forsythia suspensa «Decipiens» (Thunb.) Vahl. (72 бали) та Forsythia viridissima Lindl. (70 балів) відповідно.У результаті проведених досліджень ми визначили, що найвищу декоративність має більшість рослин Forsythia europaea Degen & Bald (бал 29-32), середня ступінь декоративності характерна для Forsythia suspensa (Thunb.) Vahl. (бал 23), відносно низький бал декоративності форзиції повислої в умовах біостаціонару ВНАУ був спричинений весняними заморозками, внаслідок чого постраждали одно- та дворічні пагони рослини, що в свою чергу негативно вплинуло на інтенсивність цвітіння виду.В результаті проведених спостережень нами було втановлено групи перспективності видів роду Forsythia Vahl. в умовах біостаціонару ВНАУ. До перспективних видів ми віднесли такі як форзиція Жиральда та форзиція середня з балом перспективності 82 і 78 відповідно. Рослини цієї групи щорічно цвітуть і плодоносять, але дещо менш зимостійкі, ніж рослини першої групи, до якої відносяться форзиція повисла та європейська.